Gender Preferences in Central and Eastern Europe as Reflected in Partnership and Fertility Outcomes - Michal Myck; Monika Oczkowska; Izabela Wowczko (Institute of Labor Economics (IZA), 2021)
The decisions of parents following the birth of their first child concerning subsequent fertility, and the stability of their relationship can be used as a reflection of broader gender preferences. We study these decisions to identify gender preferences in six Central and Eastern European countries, which vary with respect to their current political and economic conditions, but share a common experience of past communist rule. Using subsamples of census data collected in the IPUMS-International inventory around 2000 and 2010, we examine the effect of the gender of the first-born child(ren) on the fertility and relationship stability of their parents. Only in the case of Romania do our results consistently point towards boy preferences, while in Russia boy preferences can be detected in families with two or more children. Importantly, in four out of six countries (Belarus, Poland, Russia and Ukraine) parents are more likely to have a second child if the first-born was a boy, indicating girl preferences. These preferences could be interpreted as a reflection of concern regarding future care support for parents.
Keywords: J13; J16; 330; gender preferences; fertility; family structure; transition countries